Geschlechtsübergreifende Personenbezeichnungen in wissenschaftlichen Zeitschriftenartikeln: Ein deutsch-niederländischer Vergleich - Toonen, Jaron (Linguistik Online, 2022)
This study, based on a corpus of 20 Dutch and 20 German scientific journal articles, looks at how authors of German and Dutch research papers use nouns referring to persons. This investi-gation shows that although the two West Germanic languages are typologically similar due to their geographic proximity the two languages can vary a lot in terms of the abstraction (e. g. Lehrkräfte, Personen; leerkrachten, personen) and specification (e. g. Lehrerinnen und Lehrer; leraressen en leraren) of both grammatical gender and biological sex in academic articles. As a result it can be observed that Dutch authors prefer generic masculine personal nous whereas German authors tend to use more alternative forms, especially in recent times. The result contributes not only to a deeper understanding of personal nouns in academic articles but also to a clearer understanding of where and why there are differences between German and Dutch.